Al-Jawahir Fi Tafsiril Al-Qur’anil Karim Karya Tanthawi Jauhari: Kajian Tafsir Ilmi - Siti Fahimah; Dewi Ayu Lestari (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2023)
The development of commentary books is always rife, starting from the classical to contemporary periods, as well as the styles adopted by the commentators are also varied. One of the interpretations that emerged in the contemporary era is one with a scientific pattern. The mufaasir who carries this model is Thatnthawi Jauhari in his commentary al-Jawahir fi Tafsir al-Quran al-Karim. In compiling his book of commentaries, in this interpretation he reveals about the many new things in interpreting the Koran, so you don't have to stick to classic things that don't have much contribution in understanding the Koran, because of that idea many people criticize Tantawai that he is not a mufassir but a person who will understand the Koran only from the point of view of reason not naqli. This study uses a qualitative approach with the library research method. The results of this study are that Tantawi uses the tahlili method with the nuances of scientific interpretation that prioritizes ratios.